Social protection and economic integration: the politics of pension reform in era of capital mobility - Brooks, Sarah M. (2002)
In the past two decades of the 20th century, governments around the world began to apportion greater responsibility for old-age income provisions to individuals and market forces through the privatization of pension systems. This article examines the political and economic foundations of the turn to private pension systems through a quantitative analysis of 57 countries around the world. I offer a casual model to explain the likelihood and degree of pension privatization based on the unique incentives and constraints created by domestic political and economic structures in each country. I show that the existing pension system, political party structures, domestic investment and debt levels, and geopolitical networks. - Reproduced.
Keywords: Social security; Economic integration; Pensions